Professionals' Implicit Attitudes about the Competence of People Who are Blind. (July 2019) - McDonnall, Michele C.; Cmar, Jennifer L.; Antonelli, Karla; Markoski, Kasey M.
Introduction: The purpose of this study was to measure blindness professionals' implicit attitudes about the competence of people who are blind, compare implicit attitudes of blindness professionals with those of employers in hiring positions, and examine blindness professionals' implicit attitudes by type of profession and work tenure. Methods: The study included 322 blindness professionals and 450 employers. Participants completed a brief online survey and the Implicit Association Test–Blind/Visually Impaired, which measures implicit attitudes regarding the competence of blind people. Results: On average, blindness professionals exhibited a slight association, whereas employers exhibited a strong association, for sighted with competence and blind with incompetence. Blindness professionals and employers had large, statistically significant differences in implicit attitudes. Blindness professionals' implicit attitudes did not differ by type of profession, but they differed slightly by work tenure. Discussion: Employers' strong implicit bias toward sighted and competence may reflect their limited knowledge about blindness and lack of opportunities to interact with blind people. Compared to employers, blindness professionals exhibited a much smaller implicit bias, which may relate to their knowledge about blindness, exposure to successful blind people, and meaningful interactions with blind people across social contexts. Implications for practitioners: Blindness professionals may benefit from increased exposure to highly successful blind role models throughout their professional preparation programs and their careers. Blindness professionals can promote positive attitudes about blindness to the general public and to consumers and their families. During educational opportunities, they could incorporate information about how blind people perform work tasks, which has the potential to improve attitudes about the competence of blind people.